Age related changes and safety critical work: identification of tools and review of the literature - Beers, Helen; Butler, Colleen (Sudbury, 2012)
"The removal of a compulsory retirement age may have implications for health and safety at work, and as such is a cross-cutting issue for HSE. HSE is concerned that some workers may continue to perform tasks with deteriorating performance. This may be a particular issue in safety critical and major hazard industries, and could potentially lead to an increase in the risk of major incidents or injury. More generally, dutyholders may also be finding it difficult to judge whether workers have the functional capacity to work to the required level of safe performance. This piece of work has aimed to assess existing evidence on age related changes in performance and safety critical work, identify tools that assist dutyholders to assess human function and performance and to critically consider what the findings mean in terms of the need for future work."